2010
DOI: 10.1007/s00586-010-1594-4
|View full text |Cite
|
Sign up to set email alerts
|

Should smoking habit dictate the fusion technique?

Abstract: The aim of this study was to evaluate the influence of smoking on the outcome of patients undergoing surgery for degenerative spinal diseases, and to examine whether smoking had a differential impact on outcome, depending on the fusion technique used. The cohort included 120 patients treated with two different fusion techniques (translaminar screw fixation and TLIF). They were categorised with regard to their smoking habits at the time of surgery and completed the Core Outcome Measures Index at baseline and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Other studies have shown that smoking is a negative predictive factor for outcome and patient satisfaction. 38 40 Our study at an average follow-up of 4.8 years did not show smoking status to have a significant effect on patient outcome. This could again be due to the small sample size.…”
Section: Discussionmentioning
confidence: 53%
“…Other studies have shown that smoking is a negative predictive factor for outcome and patient satisfaction. 38 40 Our study at an average follow-up of 4.8 years did not show smoking status to have a significant effect on patient outcome. This could again be due to the small sample size.…”
Section: Discussionmentioning
confidence: 53%
“…In terms of surgical techniques, TLIF, when compared with TS fixation, has been shown to create a healing environment less susceptible to the detrimental effects of smoking on bony fusion. This was postulated by Luca et al 15 to be due to the fact TLIF with the presence of a cage for anterior support and posterior fixation leads to 360-degree fusion, while the TS technique with just posterior and posterolateral fusion without a cage is more susceptible to environmental factors such as smoking. We recommend that MIS-TLIF could be offered as the primary surgical option for nondiabetics patients with a positive smoking history.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Transforaminal lumbar interbody fusion (TLIF) is a standard effective procedure used in the treatment of degenerative spinal disorders. 14 In a study by Luca et al 15 comparing translaminar screw (TS) fixation and TLIF, TS smokers were found to have greater rates of nonunion than TLIF smokers. The authors postulated that the TS technique provides only largely posterior and posterolateral fusion without the presence of a cage, while TLIF group offers greater overall mechanical stability due to the presence of a cage in addition to posterior instrumentation, rendering the TLIF group less susceptible to the deleterious effects of smoking.…”
Section: Introductionmentioning
confidence: 99%
“…The nicotine in cigarette smoke has a severe vasoconstrictive effect on the microvasculature. A number of studies have shown that smoking has a negative influence on outcome in the surgical treatment of lumbar disc surgery [35]. Until now, the aforesaid studies were not conducted in terms of patient satisfaction with nursing care, which justifies our research project, providing a detailed description of the interrelations between patient satisfaction with nursing and clinical, patient-related variables in the course of surgical treatment due cervical or lumbar discopathy and degenerative spine disease.…”
Section: Discussionmentioning
confidence: 99%